Advances in intraoperative optical coherence tomography for surgical guidance. (September 2017) - El-Haddad, Mohamed T.; Tao, Yuankai K.
Abstract: Translation of optical coherence tomography (OCT) technologies for intraoperative visualization enables in vivo micron-resolution imaging of subsurface tissue structures and image-guided clinical decision-making. Over the last decade, intraoperative OCT has evolved from two-dimensional imaging using handheld probes to include biopsy-needles for minimally invasive deep-tissue imaging, surgical instrumentation using optical feedback for tremor dampening and stabilization, and stereomicroscope integrated systems that provide real-time three- and four-dimensional visualization of surgical maneuvers. In addition, several preliminary studies have demonstrated the feasibility and utility of combining intraoperative OCT imaging with novel image-processing and display methods to implement augmented/virtual reality and robotic surgical guidance platforms. While research and commercialization of these innovations have been largely driven by needs in ophthalmology, OCT is finding new clinical applications in surgical oncology and neurosurgery. In this paper, we review recent developments in intraoperative OCT and discuss current trends and future directions of the technology. Graphical abstract: Highlights: Visualization of tissue–instrument interactions during surgery is an active research area. Microscope-integrated OCT enables intraoperative imaging in ophthalmology. Integration of computational/functional image-processing methods enhances contrast. OCT-integrated instrumentation may enable robot-assisted surgery.